Pertumbuhan Kerang Darah (Tegillarca granosa) pada Berbagai Sistem Akuakultur - Kabangnga, Arnold; Heriansah, H; Nursidi, N; Kirana, Canra; Safitri, Febi (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
Many aquaculture wastes are suspended in the water column in that the presence of clams as filter feeders is required to utilize the waste for growth. In this study, blood clams from four aquaculture systems were evaluated to determine their growth, namely monoculture systems, polycultures, Integrated Multi Trophic Aquaculture (IMTA) non-paddy cocultures, and IMTA with paddy cocultures. Blood clams, tilapia, and tiger shrimp are stocked at as much as 20 each in 90 L of brackish water, whereas the density of sea cucumbers is 10 individuals. For paddy, reared using a floating method that uses trays. For four weeks, feed was given four times a day as much as 10% of the biomass. The results showed that the aquaculture system were a significant effect (P<0.05) on Spesific Growth Rate (SGR). The SGR of blood clams when combined with the IMTA systems were significantly higher (P<0.05) than that of the monoculture and polyculture systems. In contrast to growth, morphometric characteristics were not significantly affected (P>0.05) by aquaculture system. Apart from studies in laboratory scale, the highest growth of blood clams is obtained if cultured with complete trophic levels through the IMTA paddy system.